Spectral dependence of THz emission from InN and InGaN layers - Ričardas Norkus (Nature Portfolio, 2019)
Abstract Spectral dependence of terahertz emission is a sensitive tool to analyze the structure of conduction band of semiconductors. In this work, we investigate the excitation spectra of THz pulses emitted from MOCVD-grown InN and InGaN epitaxial layers with indium content of 16%, 68%, and 80%. In InN and indium-rich InGaN layers we observe a gradual saturation of THz emission efficiency with increasing photon energy. This is in stark contrast to other III-V semiconductors where an abrupt drop of THz efficiency occurs at certain photon energy due to inter-valley electron scattering. From these results, we set a lower limit of the intervalley energy separation in the conduction band of InN as 2.4 eV. In terms of THz emission efficiency, the largest optical-to-THz energy conversion rate was obtained in 75 nm thick In0.16Ga0.84N layer, while lower THz emission efficiency was observed from InN and indium-rich InGaN layers due to the screening of built-in field by a high-density electron gas in these materials.